2020
DOI: 10.1044/2020_jslhr-19-00286
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Literacy Skills at 8 Years From Preschool Language Trajectories: A Population-Based Cohort Study

Abstract: Purpose This article explored the predictive values of three main language delay (LD) trajectories (i.e., persistent, late onset, and transient) across 3–5 years on poor literacy at 8 years. Additionally, the effect of gender was assessed, using both gender-neutral and gender-specific thresholds. Method The data comprised mother-reported questionnaire data for 8,371 children in the Norwegian Mother, Father, and Child Cohort Study. Analyses were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 63 publications
2
12
0
Order By: Relevance
“…Evidence of validity based on test-criterion relationships was collected by analyzing the effects of the child's gender, maternal education, and birth order on the CDI-III-PT scores. No gender differences were found in any of the two subscales, supporting the findings of other studies that suggest that boys catch up to girls' language abilities in preschool years (Altinkaynak, 2019;Fung et al, 2019;Jin et al, 2020;van der Wilt et al, 2020). Significant effects were found for maternal education in both subscales, a result which is also congruent with the findings of previous research in early development (Umek et al, 2006;Weigel et al, 2006;Fenson et al, 2007;Richels et al, 2013;Andonova, 2015;Gonzalez et al, 2017;Cadime et al, 2018;Farley and Piasta, 2020).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Evidence of validity based on test-criterion relationships was collected by analyzing the effects of the child's gender, maternal education, and birth order on the CDI-III-PT scores. No gender differences were found in any of the two subscales, supporting the findings of other studies that suggest that boys catch up to girls' language abilities in preschool years (Altinkaynak, 2019;Fung et al, 2019;Jin et al, 2020;van der Wilt et al, 2020). Significant effects were found for maternal education in both subscales, a result which is also congruent with the findings of previous research in early development (Umek et al, 2006;Weigel et al, 2006;Fenson et al, 2007;Richels et al, 2013;Andonova, 2015;Gonzalez et al, 2017;Cadime et al, 2018;Farley and Piasta, 2020).…”
Section: Discussionsupporting
confidence: 90%
“…However, some studies with toddlers suggest that, as they approach 3;0, there is a tendency for boys to catch up in terms of expressive language (Simonsen et al, 2014). The results of other studies with preschool children, with ages ranging approximately between 3;0 and 6;0, seem to confirm that this gender gap decreases as children grow older: some studies with preschoolers show only small differences favoring girls (Jin et al, 2020;van der Wilt et al, 2020), and others do not show any differences (Altinkaynak, 2019;Fung et al, 2019).…”
Section: Sociodemographic Factors Frequently Associated With Language Developmentmentioning
confidence: 95%
“…Developmental trajectories in dyslexia can be analysed in several ways, for instance, according to psychological health (Jordan & Dyer, 2017), according to intellectual abilities (Kuppen & Goswami, 2016) or according to protective and compensatory mechanisms (Yu, Zuk, & Gaab, 2018).In line with several other studies (see, i.e., Jin et al, 2020;Peng et al, 2019;Snowling et al, 2019), the focus of this study is on literacy development as depicted by the three stages by analysing close caregivers' evaluation of their children's literacy development through kindergarten to their last year of compulsory school when they were 15 years old.…”
Section: Sample Selection and Developmental Trajectoriesmentioning
confidence: 74%
“…In MoBa, measures of communication and motor skills are included. ASQ has been used in previous studies investigating young children with language difficulties (Jin et al, 2020;Zambrana et al, 2014). The validity of ASQ has been demonstrated in a Norwegian context (Richter & Janson, 2007).…”
Section: Measurementsmentioning
confidence: 99%
“…Previous studies have found that approximately 7%-10% of children were identified as having language difficulties (Hollund-Møllerhaug, 2010;Norbury et al, 2016). Accordingly, earlier studies assessing language difficulties utilizing MoBa data have set a predefined cutoff of 1.5 SDs below the mean (Jin et al, 2020;Zambrana et al, 2014), corresponding to approximately 10%. In the current study, groups within the highest~90th percentile (indicating difficulties) were created to investigate different developmental paths of language difficulties.…”
Section: Measurementsmentioning
confidence: 99%